Kolektivní vědomí a identita volyňských Čechů pramenící z česko-ukrajinských vztahů v orálně-historickém výzkumu - Luděk Jirka (AntropoWebzin, 2011)
Changeability of czech-ukrainian relationships in multiethnic Volhynia is different envisaged from specialized literature and from respondent's narration. Czechs were comming into this area from 1868 and in spite of tsarist benefits (like nonpayment of taxis, not enter the army forces, buying farm land for cheap value) created poor inhabitants and they have to begged from Ukrainians. Agricultural knowledges and workability improved economic position of Czechs and means creation wealthier walk of life to the prejudice of Ukrainian in short temporal period. In spite of that, it didn´t provocate conflicts. Moreover, tsarist goverment prevented to rising economical position of Ukrainians, eg. by prefering collective economical development and inhibiting bussines enterprising. Social structure was etabled as disadvantage for Ukrainians and advantage for Czechs. Furthermore, Czechs inhabitants brought higher culture. Consciousness of higher social position can be seen in narration in oral history research. Respondents borned in 1918-1927 on the west Volhynia saw their life in system of social superiority (economicaly, culturaly) and these feelings are also aplicated in their history. USSR fanned nationalist movements after arrival to the West Volhynia in 1939. Activity of ukrainian nationalist atomized czech-ukrainian relationships. In spite of setting nationalist policy to USSSR regime by specialized literature, respondents mentioned it to the Nazi regime. Differences between specialized literature and oral history research is explainable, feelings and experiences from czech-ukrainian relationships in Volhynia are showing, how was created collective consciousness and identity of respondents.